Factor analysis associated with the total freight production profitability: Case study ; S.C. Tohani S.A. - Florentina Daniela Matei (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Small vineyard holdings become profitable in a market increasingly globalized, but through a process of structural adjustment supported by external and internal funds, which at this stage is essentially technical modernization in conditions of optimum size training structures, so that it can be used to the full resources available. For, ultimately, that means a higher return? Means studying the market needs to know what to produce and at what price to sell, means an optimal equipment machinery, equipment, technology etc.. That gives the vine and wine products of superior quality with minimum costs, means the effective use a well qualified workforce, tailored for the use of modern technologies, with a high labor productivity, means continuing growth of viticulture and wine quality products so that the selling price to be accepted by buyers and to sell products as easily; means a positive economic environment, characterized by a stable economy that would provide public money winnings safe so it can consume greater quantities of vine and wine products, means of export support, through appropriate economic leverage, sales just like the majority wine country.
Keywords: 330; cost; commodity production; price; marcheting wine; market